The Relationship Between Knowledge Level And Parity With Early Mobilization Activities In Post-Caesarean Section Patients At Teungku Fakinah Hospital, Banda Aceh - Putri Raihan, Putri Raihan; Eridha Putra; Ully Muzakir; Reka Julia Utama; Maulida (Teewan Journal Solutions, 2024)
Lack of knowledge about early mobilization and lack of experience in childbirth causes mothers not to do early mobilization after post-cesarean section which can impact the wound healing process. So the problem in this study is the relationship between the level of knowledge and parity with early mobilization activities in post-cesarean section patients. This study aims to determine the relationship between the level of knowledge and parity with early mobilization activities in post-cesarean section patients. The type of research used is quantitative research using a cross-sectional design. The sample collection technique used is Probability Sampling, namely stratified random sampling, obtained a sample of 75 respondents. The study was conducted by distributing questionnaires. Based on this study, the early mobilization variable shows that most of the respondents did early mobilization as many as 54 respondents (72.00%) in the knowledge variable shows that most respondents have a good level of knowledge as many as 44 respondents (58.67%) and the parity variable shows that almost half of the respondents are in multiparity parity as many as 40 respondents (53.33%) and very few in Grande Multipara parity as many as 2 respondents (2.67%). The results of the hypothesis test showed that at the level of knowledge obtained a P value = 0.000 < 0.05 and early mobilization activities obtained a P value = 0.001 < 0.05 so that Ho was rejected and Ha was accepted. It can be concluded that there is a relationship between the level of knowledge and parity with early mobilization activities in post-cesarean section mothers. Based on this study, it is recommended that post-CS patients can increase their knowledge and be given more intensive education about the importance of early mobilization, as well as be given psychological support to overcome fear or discomfort that may be experienced. In addition, it is also necessary to increase collaboration between medical personnel and patients in the planning and implementation of early mobilization. Keywords: Knowledge, Parity, Early Mobilization Activities, Caesarean Section   Kata kunci: pengetahuan, paritas, aktivitas mobilisasi dini, operasi caesar